SALTED OF HAKE IN DRY AND HUMID PILE AND FOR VACUUM OSMOTIC DEHYDRATION (MERLUCCIUS GAYI PERUANUS) - López Ráez, Luz (2005)
Three salted procedures were studied comparatively in hake fillets (Merluccius gayi peruanus): in Dry Pile (PS), Humid Pile (PH) and Vacuum Osmotic Dehydration (DOV). In the salted samples, the evolutions of the following variables were determined: Salt and water content, recount of viable aerobic microorganisms, staphylococcus, molds and water activity (aw). The population of microorganisms was found to decay quickly in samples tried with DOV.